DIVERSIDADE DE COMPOSTOS QUÍMICOS CUTICULARES DE VESPAS SOLITÁRIAS - VIEIRA, Vitória Brunetta; ANTONIALLI-JUNIOR, William Fernando; MICHELUTTI, Kamylla Balbuena; CARDOSO, Claudia Andrea Lima; ANTONIO, Denise Sguarizi (ANAIS DO ENIC, 2022)
-